Digital maturity of the organization – cognitive-methodological assumptions - Cieśliński, Wojciech (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The article presents preliminary results of research on the digital maturity of the organization. Industry 4.0 requirements, orient companies towards actions that will effectively use the latest achievements in information and communication technology. It is assumed that the level of saturation of organizations with these technologies requires organizational changes. The research results described in the article can be a stimulus for research on business transformation processes from traditional, through hybrid to digital models.